Middle Jurassic–Early Cretaceous foraminiferal biozonation of the Amran Group, eastern Sana’a Basin, Yemen - Al-Wosabi, Mohammed; El-Anbaawy, Mohammed; Al-Thour, Khalid (Geologos, 2017)
Two sections of strata assigned to the Amran Group at Jabal Salab and Jabal Yam in the eastern Sana’a governorate were sampled and correlated. These sections are part of a carbonate platform that extends from the city of Marib in the east to Naqil Ibn Ghailan, 20 km east of the city of Sana’a to the west. Palaeontological analysis of samples recovered has resulted in identification of 123 foraminiferal species, which are used to subdivide the sequence of the Amran Group into five biostratigraphic zones, aged between Bathonian (Middle Jurassic) and Berriasian (Early Cretaceous). The proposed biozones are those of Riyadhella rotundata, Kurnubia jurassica, Ammomarginulina sinaica, Alveosepta jaccardi and Pseudocyclammina sulaiyana/Furitilla caspianseis. These biozones were constructed and correlated with the equivalent zones reported from several localities.